Empowering Government Fiscal Efficiency: Usability Evaluation and E-Government Model Refinement - Khairati, Fajrul; Putra, Hasdi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the current digital transformation landscape, governments increasingly rely on electronic systems for financial management, yet the effectiveness of these systems often hinges on their usability and adaptability to evolving user needs. This study addresses these challenges by evaluating the usability of existing e-government applications for financial management and refining e-government models to enhance their efficiency, transparency, and accessibility. Through a comprehensive evaluation encompassing Nielsen's five usability categories—Learnability, Memorability, Efficiency, Error, and Satisfaction—alongside methodologies such as user surveys, usability testing, and expert evaluations, the research aims to identify areas for improvement within existing systems and refine e-government models. The expected outcomes include insights into usability challenges, empowerment of governments with more efficient fiscal management tools, and contributions to the broader discourse on optimizing public sector performance in the digital age. These efforts have the potential to significantly impact government fiscal efficiency and transparency, leading to better resource allocation, reduced waste, and increased accountability in public service delivery.